Resilience and Burnout in nurses of a general hospital in Lima, Peru - Alegre, Alberto (2019)
Background: The present study aimed to determine the relationship between resilience and burnout dimensions (emotional wear, indifference, and professional efficacy) in nurses of a general hospital in Metropolitan Lima. Method: 150 nurses were evaluated with the Maslach Burnout Inventory (MBI - GS) and with the Connor-Davidson Resilience Scale of 10 items (CD-RISC 10). The correlations between the variables were calculated and the scores were compared according to the types of shift and labor contract. . Results: There is a statistically significant relationship between resilience and burnout, being negative with the emotional stress and indifference dimensions, while with professional efficacy it was positive, obtaining small and moderate effect sizes. In addition, statistically significant differences and medium effect sizes in emotional stress and indifference were found according to the type of shift and employment contract. Conclusion: The resilience and dimensions of burnout have a significant relationship in nurses of a general hospital in Metropolitan Lima.